1997
DOI: 10.1007/bf02459297
|View full text |Cite
|
Sign up to set email alerts
|

Growth of research literature in scientific specialities. A modelling perspective

Abstract: The paper discusses the application of three well known diffusion models and their modified versions to the growth of publication data in four selected fields of S&T. It is observed that all the three models in their modified versions generally improve their performance in terms of parameter values, fit statistics, and graphical fit to the data. The most appropriate model is generally seen to be the modified exponential-logistic model. Growth of knowledgeThe understanding of the process of growth of knowledge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…It is not until a later stage that the influence on potential adopters becomes more effective in contributing to the growth in p t , and reflecting the diffusion process with the velocity defined in (6). To correct for this problem, we considered including an influencing weight factor proposed by Sharma and Bhargava (1996) and Gupta et al (1997) in the logistic function. They assumed that the adopters of scientific idea at all points of time influence the potential adopters with varying degrees of effectiveness, and such influence decreases with time.…”
Section: Concepts and Methodologymentioning
confidence: 99%
“…It is not until a later stage that the influence on potential adopters becomes more effective in contributing to the growth in p t , and reflecting the diffusion process with the velocity defined in (6). To correct for this problem, we considered including an influencing weight factor proposed by Sharma and Bhargava (1996) and Gupta et al (1997) in the logistic function. They assumed that the adopters of scientific idea at all points of time influence the potential adopters with varying degrees of effectiveness, and such influence decreases with time.…”
Section: Concepts and Methodologymentioning
confidence: 99%
“…An exponential growth in publication rate of phenological studies (as shown by a least square fit to an exponential model, R 2 = 0.96) is a common behavior for the fields of Ecology, Biometeorology or Evolution ( Fig. 1) among others, particularly after 1995 (Gupta et al, 1997;Vinkler, 2010). Even so, this increased rate of publication also shows a burgeoning interest in phenological research, more recently motivated by its insights into climate change (Cleland et al, 2007;Parmesan, 2007;Ibáñez et al, 2010;Keatley and Hudson, 2010;Chambers et al, 2013;Richardson et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…The technology life cycle is central regarding bibliometric diffusion analysis, and the majority of bibliometric diffusion studies are based on Watts and Porter's (1997) life cycle indicators. Bibliometric data can be used in determining the stage of the technology life cycle, as the growth of scientific knowledge has been observed as resembling the diffusion process, more precisely the diffusion S-curve (Gupta et al, 1997). Rogers defined the diffusion of an innovation as a process in which the innovation spreads into a social system in time, through communication between individuals (Rogers, 1962).…”
Section: Theoretical Background: Bibliometrics As a Technology Foresight Methodsmentioning
confidence: 99%